Educational Significance of Christian Moral Ideal - Dzenuškaitė, Stasė (Acta Paedagogica Vilnensia, 1993)
Especially significant for the formation of personality is the moral ideal, the content of which consists of images of the moral goal, of the perfect man, the meaning of his life. Moral ideal crystallizes in human consciousness as a single picture of a person’s life direction and content of man’s place and purpose in life. The question is, what shall be the purpose of life, what shall be the perfect man, what moral qualities shall he possess, what shall be his relationships with other people, with the closest and the most distant environment, with material and spiritual values, with himself? The answers to these questions can be given by Christianity and Christian education. The article, based on the analysis of literature and pedagogical practice, identifies the major components of the Christian moral ideal, which is based on love of God and neighbour, and discusses its influence to maturation of the personality, reflects on the conditions of its formation. It is emphasized that the formation of the moral ideal is particularly influenced by the teacher’s personality, his Christian worldview and its reflections in everyday behaviour. In order to captivate students with high moral ideals, the teacher himself must be an example in the first place.